As fronteiras da província: rotas de comércio interprovincial, Minas Gerais, 1839-1884 - Restitutti, Cristiano Corte [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
O tema desta pesquisa é o comércio interprovincial de Minas Gerais. O objetivo é identificar e caracterizar as rotas deste comércio e revisitar a série de exportações totais de Minas Gerais no século XIX, inclusive ouro e diamantes. São utilizadas fontes primárias sobre o recolhimento de impostos na fronteira mineira entre 1839 e 1884. As informações de exportações agropecuárias e de alguns itens de importação estão desagregadas por estações fiscais ao longo da fronteira. A partir destes dados foram construídas séries de quantidades comercializadas através das diferentes rotas interprovinciais. Foram construídas séries de preços de mercado para calcular o valor. As informações de preços em diversas localidades permitiram inferir sobre as articulações do mercado interno mineiro. A análise do comércio interprovincial desagregado por estações fiscais foi precedida de um esforço de regionalização, que consiste na segmentação da fronteira mineira através da percepção da diferenciação das rotas. Os resultados permitem inferir sobre possíveis origens e destinos das exportações mineiras e os movimentos de curto, médio e longo prazo no valor e composição das exportações por rota de comércio. Observam-se a importância da intermediação mercantil, a relevância dos mercados consumidores de outras províncias, as preferências por caminhos, o movimento das fronteiras agrícolas de exportação.

The subject is the commerce of Minas Gerais with other brazilian Provinces in the XIXth century. The objective is to identify and to characterize the routes of this trade and to revisit the series of total exportations of Minas Gerais, including gold and diamonds exports. The primary sources are based on the collect of taxes in the Mineiro border between 1815 and 1884. The information of agricultural, cattle and manufactures exports, and some items of importation are disaggregated per fiscal stations through the border. From these data, series of amounts commercialized through the different interprovincial routes were constructed. Series of market prices had been constructed to calculate the value. From the information of prices in diverse localities it is possible to infer on the connections of the Mineiro domestic market. The analysis of the interprovincial commerce disaggregated per fiscal stations was preceded of a regionalization effort that consists of the segmentation of the Mineiro border through the perception of the differentiation of the routes. The results allow the recognizing of possible origins and destinations of the Mineiro exportations and the movements of short, medium and long run in the value and composition for each route of trade. It is possible to observe the importance of the mercantile mediation, the relevance of the consuming markets of other provinces, the preferences for ways, the movement of the exportable agricultural cultivations.
Keywords: Comércio - Minas Gerais - 1839-1884; Brasil (Império); Minas Gerais (Província); Mercado interno; Brazil (Empire); Minas Gerais (Province); Internal market